solve for x (show steps)X2 + 20 = -9x

Question|Rated bad

Asked 3/5/2012 7:23:08 PM

Updated 8/17/2014 7:02:56 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jerry06 [8/17/2014 7:02:56 PM]

s

Expert answered|Sunshiineluv|Points 51|

Question|Rated bad

Asked 3/5/2012 7:23:08 PM

Updated 8/17/2014 7:02:56 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jerry06 [8/17/2014 7:02:56 PM]

Rating

8

x^2 + 20 = -9x

x^2 + 9x + 20 = 0

(x + 5)(x + 4) = 0

x + 5 = 0; x = -5

x + 4 = 0; x = -4

x = {-5, -4}

x^2 + 9x + 20 = 0

(x + 5)(x + 4) = 0

x + 5 = 0; x = -5

x + 4 = 0; x = -4

x = {-5, -4}

Added 8/17/2014 7:02:55 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/17/2014 7:08:29 PM]

simplify: show steps (5x – 5 ) – ( 3x – 3) **Weegy:** (5x – 5 ) – ( 3x – 3), first we have to distribute the negative, so it becomes 5x - 5 - 3x + 3. You can skip this step, but we can pair up terms to get: 5x - 3x - 5 + 3. Subtract the 3x from the 5x to get: 2x - 5 + 3. Then add the 3 to the - 5 to get: 2x - 2. Your final answer is 2x - 2. (More)

Question

Expert Answered

Updated 5/21/2014 8:49:56 AM

0 Answers/Comments

simplify: show steps (5x^2 + 3x ) + ( 2x + 5) **Weegy:** First, get rid of the parentheses. 5x^2+3x+2x+5. Second, addition. 5x^2+5x+5 Third, divide everything by 5. x^2+x+5 (More)

Question

Expert Answered

Updated 5/21/2014 8:52:24 AM

1 Answer/Comment

To get the sum of (5x^2 + 3x ) + ( 2x + 5), combine like terms.

3x and 2x are the only like terms.

3x + 2x = 5x;

The answer is 5x^2 + 5x + 5

3x and 2x are the only like terms.

3x + 2x = 5x;

The answer is 5x^2 + 5x + 5

Added 5/21/2014 8:52:24 AM

This answer has been confirmed as correct and helpful.

simplify show steps(4x – 3.5) – (3x + 1.7) **Weegy:** First, get rid of the parenthese, 4x-3.5-3x-1.7 Second, Subtraction, x-5.2. x-5.2x is the answer. (More)

Question

Expert Answered

Updated 5/21/2014 8:54:52 AM

1 Answer/Comment

(4x – 3.5) – (3x + 1.7), to get the difference,

4x - 3x = x;

-3.5 - 1.7 = -5.2

the answer is x - 5.2

4x - 3x = x;

-3.5 - 1.7 = -5.2

the answer is x - 5.2

Added 5/21/2014 8:54:51 AM

This answer has been confirmed as correct and helpful.

Simplify and show steps(8x – 2) + (7x + 6) **Weegy:** (8x – 2) + (7x + 6) = 8x - 2 + 7x + 6; = 8x + 7x - 2 + 6 = 15x + 4 (More)

Question

Expert Answered

Updated 7/15/2018 5:12:26 PM

0 Answers/Comments

Add (-5 + 6x7 + 2x5) + (9x7 + 5x5 + 9) **Weegy:** 5x5= 25 (More)

Question

Expert Answered

Updated 8/5/2014 10:58:03 PM

1 Answer/Comment

34,174,603

questions answered

There are no comments.